EFFECT OF REHABILITATION COUNSELLING ON WORK ADJUSTMENT OF INTERNALLY DISPLACED PERSONS IN CENTRAL SENATORIAL DISTRICT OF CROSS RIVER STATE - P. U, Ekpang,; Roseline A, Undie,; Mercy S., Mfon, (International Journal of Psychosocial Rehabilitation, 2020)
The study was aimed at examining the effect of rehabilitation counseling on the work adjustment of internally displaced persons in the Central Senatorial District of Cross River State. To achieve this purpose, three research questions were reviewed and three hypotheses were stated. The study adopted a pre –posttest quasi-experimental design. A purposive sampling technique was used to select the respondents for the study. The study selected a total of 154 internally displaced persons. Two camps were used for the study. The control group was made up of 74 IDPs, while the experimental group was made up of 80 persons. A pretest was first administered to them to determine their basis of comparison. A questionnaire titled Work Adjustment Scale (WAS) was used for data collection. The data were collected by the researcher and were analyzed using analysis of covariance (ANCOVA), and the result showed that there is a significant effect of rehabilitation counseling on work adjustment. However, there was no interactive effect of gender and rehabilitation counseling on work adjustment. Based on the conclusion, it was recommended that rehabilitation counseling should be provided to all people in internally displaced areas in Nigeria to offer them the opportunity to adjust appropriately to their work circumstances.